Pengaruh Penyuluhan Pertanian Terhadap Perilaku Sosial Ekonomi dan Adopsi Teknologi Petani Padi di Desa Sambong Kecamatan Ngasem Kabupaten Bojonegoro - fimarotus sofiati zuhro (Universitas Bojonegoro, 2024)
This study in Sambong Village, Bojonegoro Regency, evaluates the impact of agricultural extension on rice farmers. It finds that extension agents' roles as educators significantly enhance farmers' skills and adoption of new technologies, improving their socio-economic conditions. However, the roles of extension agents as motivators and facilitators do not significantly impact these outcomes. The model shows an R² of 0.806, indicating that the educator role explains 80.6% of the impact, with the overall model being significant. This highlights the importance of strengthening the educational role of extension agents to support farmers effectively.